2018
DOI: 10.3174/ajnr.a5872
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Hemorrhage from Iodine Using Spectral Detector CT: A Phantom Study

Abstract: BACKGROUND AND PURPOSE: Conventional CT often cannot distinguish hemorrhage from iodine extravasation following reperfusion therapy for acute ischemic stroke. We investigated the potential of spectral detector CT in differentiating these lesions. MATERIALS AND METHODS: Centrifuged blood with increasing hematocrit (5%-85%) was used to model hemorrhage. Pure blood, blood-iodine mixtures (75/25, 50/50, and 25/75 ratios), and iodine solutions (0-14 mg I/mL) were scanned in a phantom with attenuation ranging from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(3 reference statements)
0
13
0
1
Order By: Relevance
“…5,6 Dual-energy CT (DECT) has been shown effective in accurately differentiating parenchymal hemorrhage from contrast staining. 3,[7][8][9] The presence of parenchymal contrast staining on DECT immediately post-thrombectomy is associated with the development of ICH. 3,7 A retrospective study by Bonatti et al 7 of 85 patients undergoing mechanical thrombectomy showed that the presence of parenchymal hyperdensity with a maximum absolute iodine concentration of .1.35 mg/mL may identify patients developing intracerebral hemorrhage with 100% sensitivity and 67.6% specificity.…”
mentioning
confidence: 99%
“…5,6 Dual-energy CT (DECT) has been shown effective in accurately differentiating parenchymal hemorrhage from contrast staining. 3,[7][8][9] The presence of parenchymal contrast staining on DECT immediately post-thrombectomy is associated with the development of ICH. 3,7 A retrospective study by Bonatti et al 7 of 85 patients undergoing mechanical thrombectomy showed that the presence of parenchymal hyperdensity with a maximum absolute iodine concentration of .1.35 mg/mL may identify patients developing intracerebral hemorrhage with 100% sensitivity and 67.6% specificity.…”
mentioning
confidence: 99%
“…3,12 Studies focusing on dedicated abdominal protocols, including arterial, portal-venous and/or urographic phase examinations, and/ or phantoms have shown attenuation and image noise in VNC comparable to true unenhanced scans (TNC), but this has not been shown for (SDCT) into a larger patient cohort and/or focus on the liver. 3,[14][15][16] CT examinations prior to transcatheter-aortic-valvereplacements (TAVR) are increasingly applied, including unenhanced scans of the chest and CT angiography (CTA) of chest and abdomen. 17,18 This dedicated cardiac examination also depicts upper abdominal organs, such as the liver, but differs in scan and contrast media injection protocols.…”
mentioning
confidence: 99%
“…This is not a study validating the spectral CT data. While phantom studies have shown the potential of SDCT for differentiating iodine from hemorrhage [30], without verification with MRI or neuropathology we cannot completely rule out any blood extravasation on SDCT images classified as no ICH. Dual energy CT material decomposition is usually successful in neuroradiology [21].…”
Section: Limitationsmentioning
confidence: 82%